Zakat dan Intellectual Capital Pada Bank Umum Syariah di Indonesia - Tri Wahyudi; Erlina Sari Pohan; Neneng Sri Suprihatin (FEB Universitas Sultan Ageng Tirtayasa, 2020)
his study aims to analyze the performance ratio of zakat (ZPR), intellectual capital in Islamic Commercial Banks. The population period used is from 2011-2016. The sampling technique was purposive sampling and there were 57 (fiftyseven) samples that met the criteria. The analysis technique uses simple linear regression analysis. The results include intellectual capital has an influence on the zakat performance ratio (ZPR) in Islamic Commercial Banks in Indonesia.